Distribution and Depositional History of Aliphatic and Polycyclic Aromatic Hydrocarbons in River Sediments from Sarawak River, Kuching, Sarawak - Ngu, Peggy Zhen Zhen (Universiti Malaysia Sarawak (UNIMAS), 2016)
Widespread of petroleum hydrocarbon such as aliphatic hydrocarbons and polycyclic aromatic hydrocarbons (PAHs) will have harmful effects on ecosystem. However, information regarding environmental status of Sarawak River has been rare. Thus, this study was carried out to determine the spatial and vertical distribution of aliphatic and PAHs as well as to reconstruct the depositional history of these hydrocarbons in sediments. Eight surface sediment samples and five core sediment samples were collected along Sarawak River. The sediment samples were Soxhlet extracted by using dichloromethane and fractionated into aliphatic hydrocarbons (F1), PAHs (F2) and polar compounds (F3) on silica gel column chromatography. Both F1 and F2 fractions were analyzed by Gas Chromatography-Flame Ionization Detector (GC-FID), while F3 was analyzed by Gas Chromatography-Mass Spectrometer (GC-MS). This study has discovered that the n-alkanes in estuary areas (SR1 and SR2) are contributed by biogenic inputs but other stations especially SR4 and SR5 are predominantly polluted by anthropogenic influence. PAHs in sediments samples were dominated by the high molecular weight PAHs (4 to 6 rings). PAHs in core sediments are characterized by a major pyrolytic influence and minor petrogenic contamination and will occasionally pose biological impairment. The presence of oil in surface sediment of Sarawak River is confirmed by the identification of the hopane and steranes series. In conclusion, Sarawak River showed low to high level of petroleum contamination. Carbon dating analysis of sediments, quantitative analysis on hydrocarbons biomarkers and derivatization on polar fractions should be carried out in order to improve current study.